Micro-computed tomography and histomorphometric analysis of human alveolar bone repair induced by laser phototherapy: a pilot study. Issue 12 (December 2015) - Romão, M.M.A.; Marques, M.M.; Cortes, A.R.G.; Horliana, A.C.R.T.; Moreira, M.S.; Lascala, C.A.
Abstract: Immediate dental implant placement in the molar region is critical, because of the high amount of bone loss and the discrepancy between alveolar crest thickness and the implant platform. Laser phototherapy (LPT) improves bone repair. The aim of this study was to evaluate the human alveolar bone repair 40 days after molar extraction in patients submitted to LPT. Twenty patients were selected for this randomized controlled clinical trial; 10 underwent LPT (laser group) with a GaAlAs diode laser (808 nm, 100 mW, 0.04 cm 2, 75 J/cm 2, 30 s per point, 3 J per point, at five points). The control group patients ( n = 10) were not irradiated. Forty days later, the tissue formed inside the sockets was analyzed by micro-computed tomography and histomorphometry. Data from the two groups were compared with Student's t -test and Pearson's correlation test. The relative bone volume was significantly higher in the laser group ( P < 0.0001). The control group showed negative correlations ( P < 0.01) between number and thickness, and between number and separation of trabeculae, and a positive correlation between thickness and separation of trabeculae. The laser group showed a significant negative correlation between the number and thickness of trabeculae ( P < 0.01). The results suggest that LPT is able to accelerate alveolar bone repair after molar extraction, leading to a more homogeneous trabecular configuration represented by thin and close trabeculae.